Retrolaminar versus erector spinae plane block for enhanced recovery after cesarean section: a retrospective study - Bayindir, Serpil; Sanli, Cengiz (Bmc, 2026)
Background The global rise in cesarean section (CS) rates has made effective, opioid-sparing postoperative analgesia a clinical priority.The erector spinae plane block (ESPB) and retrolaminar block (RLB) are trunk blocks increasingly incorporated into multimodal analgesia protocols; however, comparative evidence between these two techniques following CS remains limited. Methods This retrospective, single-center study analyzed adult women undergoing elective CS under spinal anesthesia, without the use of general anesthesia. The primary outcome was total tramadol consumption within 24 h postoperatively. Secondary outcomes included time to first rescue analgesia, VAS scores at 1, 6, 12, and 24 h, 24-h ObsQoR-11 T score, time to discharge, and incidence of adverse events. Results Of 126 screened patients, 122 were analyzed (ESPB n = 64; RLB n = 58). ESPB significantly reduced 24-h tramadol consumption compared with RLB (130.94 mg vs. 141.9 mg;p= 0.001) and prolonged the time to first rescue analgesia (7.86 +/- 1.50 vs. 6.78 +/- 1.28 h; p = 0.001). VAS scores were significantly lower in the ESPB group at 6 h (p = 0.005) and 12 h (p < 0.001), with no differences at 1 or 24 h.ObsQoR-11 Tscores and discharge times were comparable between groups. Adverse events were infrequent; hypotension occurred in 10.9% of ESPB patients and 5.2% of RLB patients (p = 0.246). Conclusions In elective CS, ESPB provided superior early postoperative analgesia and reduced opioid consumption compared to RLB. ESPB appears to be a rational choice when prolonged analgesia and opioid sparing are prioritized in the early postoperative period, whereas RLB may serve as a reliable alternative in settings emphasizing technical and
Keywords: Cesarean section; Erector spinae plane block; Obstetric Quality-of-Recovery Score (ObsQoR-11 T); Postoperative analgesia; Recovery of function; Retrolaminar block